COVID-19 epidemic waves in Hungary and their regional distribution - Uzzoli Annamaria (Zbornik radova Departmana za geografiju, turizam i hotelijerstvo)
This paper reviews the most important spatial features of the pandemic waves in Hungary to discover their regional distribution, focusing on morbidity and mortality data. It is based on a descriptive statistical analysis examining the general epidemic situation in Hungary as well as comparing the pandemic waves. The examination also presents a general review of the COVID-19 pandemic waves and their changes in terms of space and time, exploring the typical spatial patterns. The applied regional analysis contains an examination at various geographical scales ranging from national (NUTS 1) to county (NUTS 3) and micro-regional (LAU 1) territorial levels. The most important results highlight the significant existing inequalities which can be detected among epidemic waves as well as at different territorial levels.